Global Economic Prospects : Commodity Markets Outlook, July 2014 - Baffes, John (World Bank Group, Washington, DC, 2014)
Geopolitical concerns in Iraq and Ukraine/Russia earlier in the year put upward pressure on oil prices during the second quarter. As tensions moderate, oil prices are expected to decline in 2015. Metal prices eased during the 2014Q2 due to supply response from earlier investments and weakening demand, especially by China. Weather concerns (often linked to likely El Niño) induced price increases in some grains earlier in the year but recently prices have weakened as supplies for the upcoming, 2014/15, season are deemed adequate to keep stocks at reasonable levels. Agricultural prices are expected to decline slightly in 2015. The key commodity price indices have been broadly stable during 2014Q2. Energy and agricultural prices increased 1 percent each, on geopolitical and weather-related concerns, respectively; while metal prices declined 1 percent on signs of Chinese demand weakness. The increase in beverage prices was driven by a rally in coffee prices due to dry weather in Brazil world's largest coffee supplier. Precious metal prices changed little while fertilizer prices declined 6.5 percent due to weakness in natural gas prices.